Dari Potensi Lokal ke Produk Unggulan: Pelatihan Inovasi Emping Ceplis Berbasis Pesantrenpreneur - Widyarto, Wahyu Oktri; Malik, Abdul; Wijaya, Herman; Maulana, Muhamad Reza; Anwar, Rifki; Septian, Bagas Dwi (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2026)
This community service program aimed to enhance the capacity of Islamic boarding school (pesantren) members in developing innovative melinjo-based products as an effort to support pesantren economic independence. The activity was conducted at Pondok Pesantren Al Irsyad Banten and focused on training in product innovation of emping ceplis as a diversification of traditional flat emping. The implementation method employed a participatory approach through several stages, including product potential identification, activity socialization, training on emping ceplis product innovation, and initial production mentoring. The innovation outcomes were directed to be managed under the Pesantren-Owned Enterprise (Badan Usaha Milik Pesantren / BUMPES) to ensure sustainability. The results indicate that participants were able to produce emping ceplis with several flavor variants as a form of value-added product innovation. Evaluation of participants’ understanding using a post-training questionnaire showed that the majority of participants were classified as having a very high level of understanding, indicating the effectiveness of hands-on training methods. The innovative emping ceplis products demonstrate strong potential to be developed as flagship pesantren products managed through BUMPES. Overall, this program contributes to strengthening pesantren human resource capacity and promoting sustainable local-based entrepreneurial development.